Preparation method of additive and application of additive in polycarbonate engineering plastics

By preparing Cu/TiO2-CeO2 putamen and dendritic PEG, combined with the synergistic effects of the two, an additive that can play a catalytic role in polycarbonate synthesis was prepared, which solved the problem of low catalyst efficiency in polycarbonate formation and achieved the effect of improving the yield and purity of polycarbonate.

CN119613698AActive Publication Date: 2025-03-14上海花维智能设备有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510152663.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-03-14
Estimated Expiration
2045-02-12

AI Technical Summary

Technical Problem

In the process of polycarbonate formation, efficient catalysts are needed to promote the reaction, but the prior art is difficult to effectively solve this problem.

Method used

By preparing Cu/TiO2-CeO2 putamen and dendritic PEG, combined with the synergistic effects of the two, an additive that can catalyze in polycarbonate synthesis was prepared.

Benefits of technology

The activity and redox properties of CeO2 catalyst are improved, the catalytic reaction rate is enhanced, the yield and purity of polycarbonate are improved, and the stability and recycling of additives are improved through dendritic PEG modification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613698A_ABST
    Figure CN119613698A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to a preparation method of an additive and application of the additive in polycarbonate engineering plastics. The preparation method comprises the following steps: preparing a Cu / TiO2-CeO2 shell core body; modifying with a surfactant PEG (Polyethylene Glycol); and preparing the additive. According to the invention, Cu and Ti are introduced and compounded with Ce to prepare a Cu / TiO2-CeO2 shell-core body, the synergistic effect among Cu, Ti and Ce can improve the activity of the CeO catalyst and enhance the catalytic reaction rate, meanwhile, Cu and Ti are used as a shell to increase the number of CeO surface active sites, the adsorption capacity of CeO as the catalyst to reactants is improved, and the catalytic activity of CeO is improved. Therefore, the additive prepared by taking the Cu / TiO2-CeO2 shell-core body as the main body can play a role in catalytic reaction in the preparation of the polycarbonate, and the effects of improving the yield and the purity of the polycarbonate are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a preparation method of an additive and application of the additive in polycarbonate engineering plastics. Background Art

[0002] Polycarbonate (PC) is a high-performance thermoplastic engineering plastic, which is well-known for its excellent mechanical properties, optical properties and heat resistance. It is often used in the fields of electronics, automobile industry, medical treatment, packaging, etc. The use of carbon dioxide to prepare polycarbonate is an environmentally friendly and sustainable method that can reduce dependence on traditional petroleum-based raw materials and reduce carbon emissions. This method is often referred to as one of the "green chemistry" methods. Specifically, CO2 is reacted with propylene oxide or ethylene oxide to generate cyclic carbonates, and then polycarbonate is generated through a ring-opening polymerization reaction. The advantages are mild reaction conditions and easy control. The disadvantage is that an efficient catalyst is required to promote the reaction. Therefore, the present invention provides a method for preparing an additive and its application in polycarbonate engineering plastics. The technical problem of requiring an efficient catalyst when generating polycarbonate is solved by preparing an additive that can catalyze the synthesis of polycarbonate. Summary of the invention

[0003] In view of the shortcomings of the prior art, the present invention aims to provide a method for preparing an additive.

[0004] A method for preparing an additive comprises the following steps: S1: Preparation of Cu / TiO2-CeO2 core-shell Weighing Cu(NO3)2·3H2O and adding it to ethanol, heating it in a water bath with magnetic stirring, then adding TiO2 thereto, adding an aqueous NaOH solution to obtain a metal solution, adding an aqueous glucose solution to the metal solution, filtering, washing, and drying to obtain Cu2O-TiO2, adding Cu2O-TiO2 to an ethanol solution, and sequentially adding an aqueous NaCl solution and an ethanol solution of (NH4)2Ce(NO3)6 to obtain a mixed solution, separating the mixed solution, precipitating it, drying it in a vacuum environment, and calcining the obtained Cu / TiO2-CeO2 core-shell body; S2: Surfactant PEG modification S2.1: Dissolve DMPA in dichloromethane to obtain DMPA solution, then dissolve PEG in dichloromethane to obtain PEG solution, add DPTS and DCC to the PEG solution, then add DMPA solution to obtain dendritic PEG, dissolve the dendritic PEG in methanol, add DOWEX-H + The resin is stirred and filtered, the filtrate is precipitated with ether, and the precipitated product is dried to remove the solvent to obtain the modified PEG; S3: Preparation of additives S3.1: Dissolve the Cu / TiO2-CeO2 core-shell body and modified PEG in distilled water, add NaOH solution dropwise to obtain a suspension, transfer the suspension to a hydrothermal reactor for reaction, then naturally cool to room temperature, collect the precipitate by centrifugation, dry and then heat to obtain an additive; Furthermore, the preparation of the Cu / TiO2-CeO2 core-shell body in step S1 comprises the following steps: S1.1: Weigh 0.2-0.5 parts by mass of Cu(NO3)2·3H2O and add it to ethanol, heat it in a water bath at 60°C and stir it magnetically for 5-10 minutes, then add 2 parts by mass of TiO2, stir it magnetically for 30 minutes, then add 50 parts by volume of 1 mol / L NaOH aqueous solution, and continue stirring for 30 minutes to obtain a metal solution; S1.2: Add 10 parts by volume of glucose aqueous solution to the metal solution, stir for 1 hour, and finally filter the metal solution to obtain a yellow precipitate. Wash the precipitate with deionized water and anhydrous ethanol for 3 times respectively, and then vacuum dry it at 50°C for 24 hours to obtain Cu2O-TiO2; S1.3: Add 2-2.5 parts by mass of Cu2O-TiO2 to 80 parts by volume of ethanol solution, and add 8 parts by volume of NaCl aqueous solution and 0.8-1.2 parts by mass of (NH4)2Ce(NO3)6 ethanol solution in sequence to obtain a mixed solution; S1.4: The mixture was magnetically stirred at room temperature for 30 min, then moved to a water bath and stirred at 40°C for 1 h, centrifuged to separate the solid and liquid, and the precipitate was washed three times with deionized water and dried under vacuum. Finally, the product was calcined in a muffle furnace at 400°C for 1 h to obtain a Cu / TiO2-CeO2 core-shell body.

[0005] Further, step S2 surfactant PEG modification comprises the following steps: S2.1: Dissolve 5.2 parts by mass of DMPA in 15 parts by volume of dichloromethane to obtain a DMPA solution, then dissolve 4-4.5 parts by mass of PEG in 15 parts by volume of dichloromethane to obtain a PEG solution, add 0.2-0.3 parts by mass of DPTS and 0.5-0.6 parts by mass of DCC to the PEG solution, and then add the DMPA solution; stir the reaction at room temperature for 48 hours, filter, dry the precipitated product, and remove the solvent to obtain dendritic PEG; S2.2: Dissolve the dendrimerized PEG in methanol and add DOWEX-H + The resin was stirred at room temperature for 24 h, filtered, and the filtrate was precipitated with ether. The precipitated product was dried to remove the solvent to obtain modified PEG.

[0006] Furthermore, the preparation of the additive in step S3 comprises the following steps: S3.1: Dissolve 10-12 parts by mass of Cu / TiO2-CeO2 core-shell and 0.5 parts by mass of modified PEG in 200 parts by volume of distilled water, slowly dropwise add 100 parts by volume of 11.25 mol / L NaOH solution, and stir at room temperature for 30 min to obtain a suspension; S3.2: The suspension was transferred to a hydrothermal autoclave and reacted at 110°C for 10 hours. After the reaction was completed, it was naturally cooled to room temperature. The precipitate was collected by centrifugation, washed three times with deionized water and ethanol respectively to remove impurities, and dried at 80°C for 12 hours. After drying, it was heated to 600°C in air and maintained for 3 hours to obtain the additive.

[0007] Furthermore, the solid-liquid ratio of dendrimerized PEG and methanol was 1:20 g / L.

[0008] Furthermore, the heating rate is 5°C / min.

[0009] Furthermore, the concentration of the aqueous glucose solution is 4 mol / L.

[0010] Furthermore, the concentration of the NaCl aqueous solution is 0.855 mol / L.

[0011] Furthermore, the (NH4)2Ce(NO3)6 ethanol solution is prepared by dissolving (NH4)2Ce(NO3)6 in ethanol at a solid-liquid ratio of 1:50 g / ml.

[0012] An application of an additive in polycarbonate engineering plastics comprises the following steps: L1: 3.5 parts by mass of 1,6-hexanediol, 20 parts by mass of 2-cyanopyridine and 0.5 parts by mass of additives were placed in an autoclave, the air in the autoclave was replaced with CO2 three times and then the pressure was filled to 5.0 MPa, the temperature was raised to 130°C at a rate of 3°C / min and the reaction was carried out for 8 hours. After the reaction was completed, the autoclave was naturally cooled to room temperature to obtain an intermediate; L2: Then add 30 parts by volume of CH3OH to the intermediate at 45°C for post-treatment, centrifuge for 5-20 minutes to separate the liquid and the precipitate, add 300 volumes of 4°C pre-cooled deionized water to the liquid part after removing the precipitate, store it in a refrigerator at 4°C for 12 hours, then centrifuge to recover the lower layer of liquid, and dry it in a 60°C oven for 24 hours to obtain polycarbonate.

[0013] Compared with the prior art, the present invention has at least the following beneficial effects: 1. The present invention introduces Cu and Ti and composites them with Ce to prepare a Cu / TiO2-CeO2 core-shell body. The synergistic effect between Cu and Ti and Ce can improve the activity of the CeO2 catalyst, and Cu and Ti can promote the redox performance of Ce, thereby enhancing the catalytic reaction rate. At the same time, Cu and Ti as shells increase the number of active sites on the CeO2 surface, improve the adsorption capacity of CeO2 as a catalyst for reactants, and the addition of Ti can reduce the agglomeration of CeO2 particles and prevent them from sintering at high temperatures, thereby ensuring that the additive prepared with the Cu / TiO2-CeO2 core-shell body as the main body can play a catalytic reaction in the preparation of polycarbonate, thereby improving the yield and purity of polycarbonate.

[0014] 2. The present invention dendronizes PEG by grafting DMPA. The dendronized PEG has higher water solubility due to its highly branched structure, and the dendronized PEG can be separated from the reaction system by simple physical methods such as centrifugation and filtration, which is convenient for catalyst recovery and reuse. In addition, the structure of the dendronized PEG can promote the transfer of electrons on the catalyst surface, improve the catalytic reaction rate and efficiency, and prepare additives by adding modified PEG with dendronized PEG as the main body, and apply the additives to the preparation of polycarbonate, which can greatly improve the dispersibility and solubility of the additives in the aqueous reaction system, thereby improving the purity of the polycarbonate prepared by the reaction.

[0015] 3. The present invention utilizes dendritic PEG to load Cu / TiO2-CeO2 core-shell bodies. The structure of the dendritic PEG allows it to produce a large number of internal cavities for loading the Cu / TiO2-CeO2 core-shell bodies, thereby improving the compatibility of the dendritic PEG and the Cu / TiO2-CeO2 core-shell bodies in water, effectively preventing the aggregation of the Cu / TiO2-CeO2 core-shell bodies, and improving their stability during the reaction, thereby improving the purity of the polycarbonate. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, further serve to explain the principles of the invention and to enable those skilled in the relevant art to make and use the invention.

[0017] Figure 1 The present invention is a flowchart of a method for preparing an additive used in an embodiment of the present invention. DETAILED DESCRIPTION

[0018] The following is a detailed description of a preparation method of an additive provided by the present invention in conjunction with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternatives to implement some known technologies; and the accompanying drawings are only for more specific description of the embodiments, and are not intended to specifically limit the present invention.

[0019] Embodiment 1: A method for preparing an additive, such as Figure 1 As shown, the following steps are included: S1: Preparation of Cu / TiO2-CeO2 core-shell S1.1: Weigh 0.2 parts by mass of Cu(NO3)2·3H2O and add it to ethanol, heat it in a water bath at 60°C and stir it magnetically for 5-10 minutes, then add 2 parts by mass of TiO2, stir it magnetically for 30 minutes, then add 50 parts by volume of 1 mol / L NaOH aqueous solution, and continue stirring for 30 minutes to obtain a metal solution; S1.2: Add 10 parts by volume of 4 mol / L glucose aqueous solution to the metal solution, stir for 1 hour, and finally filter the metal solution to obtain a yellow precipitate. Wash the precipitate with deionized water and anhydrous ethanol for 3 times, and then vacuum dry it at 50°C for 24 hours to obtain Cu2O-TiO2; S1.3: Add 2 parts by mass of Cu2O-TiO2 to 80 parts by volume of ethanol solution, and add 8 parts by volume of 0.855 mol / L NaCl aqueous solution and 0.8 parts by mass of (NH4)2Ce(NO3)6 ethanol solution in sequence, wherein the (NH4)2Ce(NO3)6 ethanol solution is prepared by dissolving (NH4)2Ce(NO3)6 in ethanol at a solid-liquid ratio of 1:50 g / ml to obtain a mixed solution; S1.4: The mixture was magnetically stirred at room temperature for 30 min, then moved to a water bath and stirred at 40°C for 1 h, centrifuged to separate the solid and liquid, and the precipitate was washed three times with deionized water and dried under vacuum. Finally, the product was calcined in a muffle furnace at 400°C for 1 h to obtain a Cu / TiO2-CeO2 core-shell body.

[0020] S2: Surfactant PEG modification S2.1: Dissolve 5.2 parts by mass of DMPA in 15 parts by volume of dichloromethane to obtain a DMPA solution, then dissolve 4 parts by mass of PEG in 15 parts by volume of dichloromethane to obtain a PEG solution, add 0.2 parts by mass of DPTS and 0.5-0.6 parts by mass of DCC to the PEG solution, and then add the DMPA solution; stir the reaction at room temperature for 48 hours, filter, dry the precipitated product, and remove the solvent to obtain dendritic PEG; S2.2: Dissolve the dendrimerized PEG in methanol, with the ratio of dendrimerized PEG to methanol being 1:20 g / L, and add DOWEX-H + The resin was stirred at room temperature for 24 h, filtered, and the filtrate was precipitated with ether. The precipitated product was dried to remove the solvent to obtain modified PEG.

[0021] S3: Preparation of additives S3.1: 12 parts by mass of Cu / TiO2-CeO2 core-shell and 0.5 parts by mass of modified PEG were dissolved in 200 parts by volume of distilled water, 100 parts by volume of 11.25 mol / L NaOH solution was slowly added dropwise, and stirred at room temperature for 30 min to obtain a suspension; S3.2: The suspension was transferred to a hydrothermal autoclave and reacted at 110°C for 10 hours. After the reaction was completed, it was naturally cooled to room temperature. The precipitate was collected by centrifugation, washed three times with deionized water and ethanol respectively to remove impurities, and dried at 80°C for 12 hours. After drying, it was heated to 600°C in air at a heating rate of 5°C / min and maintained for 3 hours to obtain the additive.

[0022] Application of additives L1: 3.5 parts by mass of 1,6-hexanediol, 20 parts by mass of 2-cyanopyridine and 0.5 parts by mass of additives were placed in an autoclave, the air in the autoclave was replaced with CO2 three times and then the pressure was filled to 5.0 MPa, the temperature was raised to 130°C at a rate of 3°C / min and the reaction was carried out for 8 hours. After the reaction was completed, the autoclave was naturally cooled to room temperature to obtain an intermediate; L2: Then add 30 parts by volume of CH3OH to the intermediate at 45°C for post-treatment, centrifuge for 20 minutes to separate the liquid and the precipitate, add 300 volumes of pre-cooled deionized water to the liquid part after removing the precipitate, store it in a refrigerator at 4°C for 12 hours, then centrifuge to recover the lower layer of liquid, and place it in a 60°C oven to dry for 24 hours to obtain polycarbonate.

[0023] Embodiment 2: A method for preparing an additive, such as Figure 1 As shown, the following steps are included: S1: Preparation of Cu / TiO2-CeO2 core-shell S1.1: Weigh 0.5 parts by mass of Cu(NO3)2·3H2O and add it to ethanol, heat it in a water bath at 60°C and stir it magnetically for 5-10 minutes, then add 2 parts by mass of TiO2, stir it magnetically for 30 minutes, then add 50 parts by volume of 1 mol / L NaOH aqueous solution, and continue stirring for 30 minutes to obtain a metal solution; S1.2: Add 10 parts by volume of 4 mol / L glucose aqueous solution to the metal solution, stir for 1 hour, and finally filter the metal solution to obtain a yellow precipitate. Wash the precipitate with deionized water and anhydrous ethanol for 3 times, and then vacuum dry it at 50°C for 24 hours to obtain Cu2O-TiO2; S1.3: Add 2 parts by mass of Cu2O-TiO2 to 80 parts by volume of ethanol solution, and add 8 parts by volume of 0.855 mol / L NaCl aqueous solution and 0.8 parts by mass of (NH4)2Ce(NO3)6 ethanol solution in sequence, wherein the (NH4)2Ce(NO3)6 ethanol solution is prepared by dissolving (NH4)2Ce(NO3)6 in ethanol at a solid-liquid ratio of 1:50 g / ml to obtain a mixed solution; S1.4: The mixture was magnetically stirred at room temperature for 30 min, then moved to a water bath and stirred at 40°C for 1 h, centrifuged to separate the solid and liquid, and the precipitate was washed three times with deionized water and dried under vacuum. Finally, the product was calcined in a muffle furnace at 400°C for 1 h to obtain a Cu / TiO2-CeO2 core-shell body.

[0024] S2: Surfactant PEG modification S2.1: Dissolve 5.2 parts by mass of DMPA in 15 parts by volume of dichloromethane to obtain a DMPA solution, then dissolve 4 parts by mass of PEG in 15 parts by volume of dichloromethane to obtain a PEG solution, add 0.2 parts by mass of DPTS and 0.5-0.6 parts by mass of DCC to the PEG solution, and then add the DMPA solution; stir the reaction at room temperature for 48 hours, filter, dry the precipitated product, and remove the solvent to obtain dendritic PEG; S2.2: Dissolve the dendrimerized PEG in methanol, with the ratio of dendrimerized PEG to methanol being 1:20 g / L, and add DOWEX-H + The resin was stirred at room temperature for 24 h, filtered, and the filtrate was precipitated with ether. The precipitated product was dried to remove the solvent to obtain modified PEG.

[0025] S3: Preparation of additives S3.1: Dissolve 10 parts by mass of Cu / TiO2-CeO2 core-shell and 0.5 parts by mass of modified PEG in 200 parts by volume of distilled water, slowly dropwise add 100 parts by volume of 11.25 mol / L NaOH solution, and stir at room temperature for 30 min to obtain a suspension; S3.2: The suspension was transferred to a hydrothermal autoclave and reacted at 110°C for 10 hours. After the reaction was completed, it was naturally cooled to room temperature. The precipitate was collected by centrifugation, washed three times with deionized water and ethanol respectively to remove impurities, and dried at 80°C for 12 hours. After drying, it was heated to 600°C in air at a heating rate of 5°C / min and maintained for 3 hours to obtain the additive.

[0026] Application of additives L1: 3.5 parts by mass of 1,6-hexanediol, 20 parts by mass of 2-cyanopyridine and 0.5 parts by mass of additives were placed in an autoclave, the air in the autoclave was replaced with CO2 three times and then the pressure was filled to 5.0 MPa, the temperature was raised to 130°C at a rate of 3°C / min and the reaction was carried out for 8 hours. After the reaction was completed, the autoclave was naturally cooled to room temperature to obtain an intermediate; L2: Then add 30 parts by volume of CH3OH to the intermediate at 45°C for post-treatment, centrifuge for 20 minutes to separate the liquid and the precipitate, add 300 volumes of pre-cooled deionized water to the liquid part after removing the precipitate, store it in a refrigerator at 4°C for 12 hours, then centrifuge to recover the lower layer of liquid, and place it in a 60°C oven to dry for 24 hours to obtain polycarbonate.

[0027] Embodiment 3: A method for preparing an additive, such as Figure 1 As shown, the following steps are included: S1: Preparation of Cu / TiO2-CeO2 core-shell S1.1: Weigh 0.2 parts by mass of Cu(NO3)2·3H2O and add it to ethanol, heat it in a water bath at 60°C and stir it magnetically for 5-10 minutes, then add 2 parts by mass of TiO2, stir it magnetically for 30 minutes, then add 50 parts by volume of 1 mol / L NaOH aqueous solution, and continue stirring for 30 minutes to obtain a metal solution; S1.2: Add 10 parts by volume of 4 mol / L glucose aqueous solution to the metal solution, stir for 1 hour, and finally filter the metal solution to obtain a yellow precipitate. Wash the precipitate with deionized water and anhydrous ethanol for 3 times, and then vacuum dry it at 50°C for 24 hours to obtain Cu2O-TiO2; S1.3: Add 2.5 parts by mass of Cu2O-TiO2 to 80 parts by volume of ethanol solution, and add 8 parts by volume of 0.855 mol / L NaCl aqueous solution and 1.2 parts by mass of (NH4)2Ce(NO3)6 ethanol solution in sequence, wherein the (NH4)2Ce(NO3)6 ethanol solution is prepared by dissolving (NH4)2Ce(NO3)6 in ethanol at a solid-liquid ratio of 1:50 g / ml to obtain a mixed solution; S1.4: The mixture was magnetically stirred at room temperature for 30 min, then moved to a water bath and stirred at 40°C for 1 h, centrifuged to separate the solid and liquid, and the precipitate was washed three times with deionized water and dried under vacuum. Finally, the product was calcined in a muffle furnace at 400°C for 1 h to obtain a Cu / TiO2-CeO2 core-shell body.

[0028] S2: Surfactant PEG modification S2.1: Dissolve 5.2 parts by mass of DMPA in 15 parts by volume of dichloromethane to obtain a DMPA solution, then dissolve 4 parts by mass of PEG in 15 parts by volume of dichloromethane to obtain a PEG solution, add 0.2 parts by mass of DPTS and 0.5-0.6 parts by mass of DCC to the PEG solution, and then add the DMPA solution; stir the reaction at room temperature for 48 hours, filter, dry the precipitated product, and remove the solvent to obtain dendritic PEG; S2.2: Dissolve the dendrimerized PEG in methanol, with the ratio of dendrimerized PEG to methanol being 1:20 g / L, and add DOWEX-H + The resin was stirred at room temperature for 24 h, filtered, and the filtrate was precipitated with ether. The precipitated product was dried to remove the solvent to obtain modified PEG.

[0029] S3: Preparation of additives S3.1: 12 parts by mass of Cu / TiO2-CeO2 core-shell and 0.5 parts by mass of modified PEG were dissolved in 200 parts by volume of distilled water, 100 parts by volume of 11.25 mol / L NaOH solution was slowly added dropwise, and stirred at room temperature for 30 min to obtain a suspension; S3.2: The suspension was transferred to a hydrothermal autoclave and reacted at 110°C for 10 hours. After the reaction was completed, it was naturally cooled to room temperature. The precipitate was collected by centrifugation, washed three times with deionized water and ethanol respectively to remove impurities, and dried at 80°C for 12 hours. After drying, it was heated to 600°C in air at a heating rate of 5°C / min and maintained for 3 hours to obtain the additive.

[0030] Application of additives L1: 3.5 parts by mass of 1,6-hexanediol, 20 parts by mass of 2-cyanopyridine and 0.5 parts by mass of additives were placed in an autoclave, the air in the autoclave was replaced with CO2 three times and then the pressure was filled to 5.0 MPa, the temperature was raised to 130°C at a rate of 3°C / min and the reaction was carried out for 8 hours. After the reaction was completed, the autoclave was naturally cooled to room temperature to obtain an intermediate; L2: Then add 30 parts by volume of CH3OH to the intermediate at 45°C for post-treatment, centrifuge for 5 minutes to separate the liquid and the precipitate, add 300 volumes of pre-cooled deionized water to the liquid part after removing the precipitate, store it in a refrigerator at 4°C for 12 hours, then centrifuge to recover the lower layer of liquid, and place it in a 60°C oven to dry for 24 hours to obtain polycarbonate.

[0031] Comparative Example 1: Compared with Example 1, the difference of Comparative Example 1 is that step S1 is not performed, and CeO2 is directly added in step S3 to prepare the additive, specifically: "S3.1: 12 parts by mass of CeO2 and 0.5 parts by mass of modified PEG are dissolved in 200 parts by volume of distilled water, 100 parts by volume of NaOH solution with a concentration of 11.25 mol / L is slowly added dropwise, and stirred at room temperature for 30 min to obtain a suspension; S3.2: The suspension is transferred to a hydrothermal reactor and reacted at 110°C for 10 hours. After the reaction is completed, the suspension is naturally cooled to room temperature. The precipitate is collected by centrifugation, washed three times with deionized water and ethanol respectively to remove impurities, and dried at 80°C for 12 hours. After drying, the suspension is heated to 600°C in air and maintained for 3 hours to obtain an additive. The prepared additive is used to prepare polycarbonate, and the yield and purity of the polycarbonate are tested and calculated.

[0032] Comparative Example 2: Compared with Example 1, the difference of Comparative Example 2 is that step S2 is not performed, and PEG is directly added in step S3 to prepare the additive, specifically: "S3.1: 12 parts by mass of Cu / TiO2-CeO2 core-shell body and 0.5 parts by mass of PEG are dissolved in 200 parts by volume of distilled water, 100 parts by volume of NaOH solution with a concentration of 11.25 mol / L is slowly added dropwise, and stirred at room temperature for 30 min to obtain a suspension; S3.2: The suspension is transferred to a hydrothermal reactor and reacted at 110°C for 10 hours. After the reaction is completed, the suspension is naturally cooled to room temperature. The precipitate is collected by centrifugation, washed three times with deionized water and ethanol respectively to remove impurities, and dried at 80°C for 12 hours. After drying, the suspension is heated to 600°C in air at a heating rate of 5°C / min and maintained for 3 hours to obtain an additive. The prepared additive is used to prepare polycarbonate, and the yield and purity of the polycarbonate are tested and calculated.

[0033] The yield and purity of the polycarbonate prepared in Examples 1-3 and Comparative Examples 1-2 are shown in Table 1 below.

[0034]

[0035] The yields of Examples 1-3 were 92.5%, 91.7% and 92.2%, respectively, and the purities were all 95%. It can be seen that the yield and purity of the additive prepared by loading the Cu / TiO2-CeO2 core-shell body with dendritic PEG were better than those of the control example.

[0036] The yield of Comparative Example 1 is 79.6% and the purity is 91%. It can be seen that the additive prepared by CeO2 without the introduction of Cu and Ti has a reduced catalytic effect on polycarbonate, and the yield and purity are also reduced.

[0037] The yield of Comparative Example 2 was 83.8% and the purity was 89%. It can be seen that PEG without dendronization could not improve the stability of the additive, resulting in a decrease in the yield and purity of the polycarbonate.

[0038] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing an additive, characterized in that: The steps include: S1: Preparation of Cu / TiO2-CeO2 core-shell Weighing Cu(NO3)2·3H2O and adding it to ethanol, heating it in a water bath with magnetic stirring, then adding TiO2 thereto, adding an aqueous NaOH solution to obtain a metal solution, adding an aqueous glucose solution to the metal solution, filtering, washing, and drying to obtain Cu2O-TiO2, adding Cu2O-TiO2 to an ethanol solution, and sequentially adding an aqueous NaCl solution and an ethanol solution of (NH4)2Ce(NO3)6 to obtain a mixed solution, separating the mixed solution, precipitating it, drying it in a vacuum environment, and calcining the obtained Cu / TiO2-CeO2 core-shell body; S2: Surfactant PEG modification S2.1: Dissolve DMPA in dichloromethane to obtain DMPA solution, then dissolve PEG in dichloromethane to obtain PEG solution, add DPTS and DCC to the PEG solution, then add DMPA solution to obtain dendritic PEG, dissolve the dendritic PEG in methanol, add DOWEX-H + The resin is stirred and filtered, the filtrate is precipitated with ether, and the precipitated product is dried to remove the solvent to obtain the modified PEG; S3: Preparation of additives S3.1: Dissolve the Cu / TiO2-CeO2 core-shell and modified PEG in distilled water, add NaOH solution dropwise to obtain a suspension, transfer the suspension to a hydrothermal kettle for reaction, then naturally cool to room temperature, collect the precipitate by centrifugation, dry and then heat to obtain an additive.

2. The method for preparing an additive according to claim 1, characterized in that: Step S1: Preparation of Cu / TiO2-CeO2 core-shell body, comprising the following steps: S1.1: Weigh 0.2-0.5 parts by mass of Cu(NO3)2·3H2O and add it to ethanol, heat it in a water bath at 60°C and stir it magnetically for 5-10 minutes, then add 2 parts by mass of TiO2, stir it magnetically for 30 minutes, then add 50 parts by volume of 1 mol / L NaOH aqueous solution, and continue stirring for 30 minutes to obtain a metal solution; S1.2: Add 10 parts by volume of glucose aqueous solution to the metal solution, stir for 1 hour, and finally filter the metal solution to obtain a yellow precipitate. Wash the precipitate with deionized water and anhydrous ethanol for 3 times respectively, and then vacuum dry it at 50°C for 24 hours to obtain Cu2O-TiO2; S1.3: Add 2-2.5 parts by mass of Cu2O-TiO2 to 80 parts by volume of ethanol solution, and add 8 parts by volume of NaCl aqueous solution and 0.8-1.2 parts by mass of (NH4)2Ce(NO3)6 ethanol solution in sequence to obtain a mixed solution; S1.4: The mixture was magnetically stirred at room temperature for 30 min, then moved to a water bath and stirred at 40°C for 1 h, centrifuged to separate the solid and liquid, and the precipitate was washed three times with deionized water and dried under vacuum. Finally, the product was calcined in a muffle furnace at 400°C for 1 h to obtain a Cu / TiO2-CeO2 core-shell body.

3. The method for preparing an additive according to claim 2, characterized in that: Step S2 surfactant PEG modification comprises the following steps: S2.1: Dissolve 5.2 parts by mass of DMPA in 15 parts by volume of dichloromethane to obtain a DMPA solution, then dissolve 4-4.5 parts by mass of PEG in 15 parts by volume of dichloromethane to obtain a PEG solution, add 0.2-0.3 parts by mass of DPTS and 0.5-0.6 parts by mass of DCC to the PEG solution, and then add the DMPA solution; stir the reaction at room temperature for 48 hours, filter, dry the precipitated product, and remove the solvent to obtain dendritic PEG; S2.2: Dissolve the dendrimerized PEG in methanol and add DOWEX-H + The resin was stirred at room temperature for 24 h, filtered, and the filtrate was precipitated with ether. The precipitated product was dried to remove the solvent to obtain modified PEG.

4. The method for preparing an additive according to claim 3, characterized in that: Step S3: Preparation of additives, comprising the following steps: S3.1: Dissolve 10-12 parts by mass of Cu / TiO2-CeO2 core-shell and 0.5 parts by mass of modified PEG in 200 parts by volume of distilled water, slowly dropwise add 100 parts by volume of 11.25 mol / L NaOH solution, and stir at room temperature for 30 min to obtain a suspension; S3.2: The suspension was transferred to a hydrothermal autoclave and reacted at 110°C for 10 hours. After the reaction was completed, it was naturally cooled to room temperature. The precipitate was collected by centrifugation, washed three times with deionized water and ethanol respectively to remove impurities, and dried at 80°C for 12 hours. After drying, it was heated to 600°C in air and maintained for 3 hours to obtain the additive.

5. The method for preparing an additive according to claim 4, characterized in that: The solid-liquid ratio of dendrimerized PEG and methanol was 1:20 g / L.

6. The method for preparing an additive according to claim 5, characterized in that: The heating rate is 5°C / min.

7. The method for preparing an additive according to claim 6, characterized in that: The concentration of the glucose aqueous solution is 4 mol / L.

8. The method for preparing an additive according to claim 7, characterized in that: The concentration of the NaCl aqueous solution is 0.855 mol / L.

9. The method for preparing an additive according to claim 8, characterized in that: The (NH4)2Ce(NO3)6 ethanol solution is prepared by dissolving (NH4)2Ce(NO3)6 in ethanol at a solid-liquid ratio of 1:50 g / ml.

10. Use of an additive in polycarbonate engineering plastics according to claim 9, characterized in that: The steps include: L1: 3.5 parts by mass of 1,6-hexanediol, 20 parts by mass of 2-cyanopyridine and 0.5 parts by mass of additives were placed in an autoclave, the air in the autoclave was replaced with CO2 three times and then the pressure was filled to 5.0 MPa, the temperature was raised to 130°C at a rate of 3°C / min and the reaction was carried out for 8 hours. After the reaction was completed, the autoclave was naturally cooled to room temperature to obtain an intermediate; L2: Then add 30 parts by volume of CH3OH to the intermediate at 45°C for post-treatment, centrifuge for 5-20 minutes to separate the liquid and the precipitate, add 300 volumes of 4°C pre-cooled deionized water to the liquid part after removing the precipitate, store it in a refrigerator at 4°C for 12 hours, then centrifuge to recover the lower layer of liquid, and dry it in a 60°C oven for 24 hours to obtain polycarbonate.

Citation Information

Patent Citations

  • Method for preparing polycarbonate

    CN104031256A

  • Modifying additive for enhancing scratch resistance and stain resistance of polycarbonate engineering plastic

    CN108976750A

  • Copper-cerium-based core-shell catalyst and preparation method thereof

    CN119386879A